EARLOBE KELOID: A REVIEW OF TREATMENT OPTIONS - Batubara, Dian Erisyawanty (Medicina Biomedica Journal, 2022)
Earlobe keloids are fibrous proliferations that show high recurrency. Therefore these benign lessions become one of the challenging and frustrating problem in wound healing. This affect people worldwide with different rases. The treatment of earlobe keloid is still challenging. Many different treatment options have been used to reduce the recurrency of earlobe keloid with various results, such as surgical excision, injection of ingtralessional corticosteroid and cryotherapy, however no single treatment modalities have been given satisfying results. In this artcle, we reviewed various treatment options of earlobe keloid from many different countries.